2000
DOI: 10.1046/j.1365-313x.2000.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of putative anion channel gene AtCLC‐a in Arabidopsis suggests a role in the regulation of nitrate content

Abstract: SummaryIn animals and yeast, voltage-dependent chloride channels of the CLC family play a role in basic cellular functions such as epithelial transport, plasma membrane excitability, and control of pH and membrane potential in intracellular compartments. To assess the function of CLCs in plants, we searched for CLC insertion mutants in a library of Arabidopsis lines transformed by Agrobacterium tumefaciens transferred DNA (T-DNA). Using a polymerase chain reaction-based screening procedure, an Arabidopsis line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 34 publications
8
128
1
1
Order By: Relevance
“…Fourteen mutants were obtained for genes potentially controlling nitrate levels, and nine and 15 mutants were recovered from the phosphate and sulfate sets, respectively (Supplemental Table S4). For the CLC-A gene, a previously described clca-1 mutant in the Wassilewskija (Ws) background (Geelen et al, 2000) was provided by Sébastien Thomine at the Centre National de la Recherche Scientifique. These mutants were grown in controlled-environment conditions, and anion levels in leaves were determined (Fig.…”
Section: Analysis Of Candidate Genesmentioning
confidence: 99%
“…Fourteen mutants were obtained for genes potentially controlling nitrate levels, and nine and 15 mutants were recovered from the phosphate and sulfate sets, respectively (Supplemental Table S4). For the CLC-A gene, a previously described clca-1 mutant in the Wassilewskija (Ws) background (Geelen et al, 2000) was provided by Sébastien Thomine at the Centre National de la Recherche Scientifique. These mutants were grown in controlled-environment conditions, and anion levels in leaves were determined (Fig.…”
Section: Analysis Of Candidate Genesmentioning
confidence: 99%
“…One candidate gene family is the CLC family, because CLC homologs in prokaryotes mediate Cl À flux. However to date, none of the seven CLC family members in Arabidopsis has been localized to the PM or shown to function as an anion channel in planta [84,85]. Another candidate gene family is the ATP-binding cassette (ABC) superfamily [86,87].…”
Section: Anion Channels: Properties and Regulationmentioning
confidence: 99%
“…OsClC1 and OsClC2 proteins, both closely related with AtClCc, were localized at the vacuolar membrane using both immunochemical detection methods and transient expression of GFP fusions (Nakamura et al 2006). Whereas loss-of-function mutants for OsClC1 and 2 genes exhibit reduced growth at all life stages (Nakamura et al 2006) (Geelen et al 2000). In agreement with the chloroplast localization of AtClCe, the clce mutants showed altered photosynthetic activity (Marmagne et al 2007), but their nitrate content is also reduced as observed in clca mutants ( D. Monachello & G. Ephritikhine 2007, personal communication).…”
Section: The Plant Clc Familymentioning
confidence: 99%